Sustainable additive manufacturing of recycled RPU/PLA composites via filament extrusion for enhanced mechanical and acoustic properties - Vinoth Kumar Selvaraj; Jeyanthi Subramanian; Ravi Seenivasan; B․G Sai Charan; Bhaherathi S; Aachal Vinayak Kulkarni; Vinod Ayyappan; Sanjay Mavinkere Rangappa; Suchart Siengchin (Results in Engineering, 2025)
Recycling rigid polyurethane (PU) waste remains a challenge due to its complex chemical structure and non-biodegradability. This study introduces a novel approach to recycling rigid PU by incorporating it into polylactic acid (PLA) to create composite filaments compatible with fused deposition modeling (FDM) 3D printing. The mechanical (tensile and flexural) and acoustic properties of the printed samples were systematically evaluated through experimental analysis and validated via simulations. The 3 wt.% rigid PU-PLA composites exhibited the highest mechanical strength, with a 10.3 % increase in ultimate tensile strength (32 N/mm2) compared to pristine PLA (29 N/mm2). The flexural strength peaked at 55 N/mm2 at 3.7 % strain for the 3 wt.% rigid PU sample. While higher rigid PU content (>3 wt.%) led to mechanical performance degradation due to particle agglomeration and reduced interfacial adhesion, the 6 wt.% rigid PU composite exhibited the highest acoustic performance, achieving a maximum absorption coefficient (α = 0.35 at 1350 Hz) and sound pressure level (SPL) reductions of 30–55 dB. High-resolution scanning electron microscopy (HR-SEM), thermogravimetric analysis (TGA), and Fourier transform infrared spectroscopy (FTIR) provided insights into the composite’s morphology, chemical interactions, and thermal stability. This work presents a sustainable strategy for rigid PU waste recycling, improving both the mechanical strength and acoustic properties of PLA composites to be used in high-performance engineering applications.